Existence of Weak Solutions for the Class of Singular Two-Phase Problems with a ?-Hilfer Fractional Operator and Variable Exponents - Bouali T.; Guefaifia R.; Jan R.; Boulaaras S.; Radwan T. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
In this paper, we prove the existence of at least two weak solutions to a class of singular two-phase problems with variable exponents involving a ?-Hilfer fractional operator and Dirichlet-type boundary conditions when the term source is dependent on one parameter. Here, we use the fiber method and the Nehari manifold to prove our results. ? 2024 by the authors.